After This, Nothing Happened: Indigenous Academic Writing and Chickadee Peoples’ Words - Koptie, Steve (First Peoples Child & Family Review, 2009)
Canadian Indigenous scholars valiantly search for stores of resilience and strength in contemporary Canada to demystify the tragic place of Indians in Canada. It is very much a journey of self-discovery and recovery of a positive identity and lost human dignity that allows the restoration of pride to succeed with the gifts Creation provides to Indigenous peoples. Cook- Lynn (2007) addresses this quest to locate safe places of connecting to those stories in her important work Anti-Indianism in Modern America: Voice from Tatekeya’s Earth, where she writes about the obligation of Indigenous scholars to project strong voices to people who “believe in the stereotypical assumption that Indians are ‘damned’.. vanished, or pathetic remnants of a race” and “let’s get rid of Indian reservations” or “let’s abrogate Indian treaties.” Instead of feeling inspired to find places of good will far too much energy is sapped escaping spaces of hate, indifference and inexcusable innocence. The cultural, historical and social confusion of a one-sided portrayal of Canadian colonization creates for researchers/witnesses at all levels of education huge gaps in understanding the unresolved pain and injury of Canada’s colonial past on Canada’s First Nations. Indigenous peoples are invisible in most areas of academic study, normally relegated to special programs like Aboriginal Studies as if Indigenous world-views, knowledge, culture and vision for Canada’s future required mere comma’s in course material that feel like “oh yea, then there are aboriginal people who feel” that stand for inclusion but feel like after thoughts only if a visible “Indian” finds a seat in the class. Indigenous students’ experience within the academy has is often a ‘Dickenish’ tale. It is a tale of two extremes; the best of times and the worst of times mostly simultaneously as each glorious lesson learned carries the lonely burden of responsibility to challenge the shame and humiliation of each racist, ignorant and arrogant colonial myth perpetuated. Like Oliver Twist we want more. This paper was conceived out of an invitation by Indigenous author Lee Maracle at the 2009 University of Toronto SAGE (Supporting Aboriginal Graduate Enhancement) writing retreat where Lee and the Cree Elder Pauline Shirt spun webs of stories to encourage Indigenous scholars to explore and express our survival of vicious, traumatic and intentional cultural upheavals.